PERKEBUNAN KARET DI SINTANG PADA AWAL ABAD KE-20 (KAJIAN SOSIAL EKONOMI) - Eka Jaya Putra Utama; Nunik Esti Utami; Basuki Wibowo; Riska Chaya W (Khazanah Pendidikan, 2020)
ABSTRACTThis study aims to describe the process of planting and distributing rubber products inSintang, and the process of rubber trading in Sintang in the early 20th century. Researchconducted by the historical method, the data obtained using oral history in the form ofinterviews and analyzing documents. The results showed that rubber plantations inSintang were scattered in several regions, one of which was located in Nanga JetakVillage. The preparation of the sap seeds has been prepared by the Dutch Indiesbusinessman, then distributed to various regions in Sintang. Cultivation of rubber plantswas carried out by indigenous people and assisted by Javanese people who werecontacted by Dutch Indies businessmen as rubber farmers. Rubber plantations aremanaged by Dutch Indies businessmen and some Chinese. Rubber that has beenprocessed into sap is sent to the kingdom of Sintang through the Melawi River and theDutch East Indies Government in Pontianak via the Kapuas RiverKeyword: rubber plantation, Sintang, social-economic history.